Is Small Better? A Comparison of the Effect of Large and Small Dams on Cropland Productivity in South Africa - Blanc, Elodie; Strobl, Eric (World Bank, Washington, DC, 2013)
This study estimates and compares the effects of small and large irrigation dams on cropland productivity in South Africa. To this end, a panel data set of South African river basins is constructed. The econometric analysis reveals that although large dams increase cropland productivity downstream, they have a negative effect on cropland within the vicinity. However, their existence can enhance the relatively small positive impact of local small dams. Although a cost-benefit analysis of irrigation benefits shows that small dams may be more viable than large ones, large dams can play a potentially important role within a system of both types of dams.